Reinforcing EU Governance in Times of Crisis: The Commission Proposals and Beyond - Ansgar Belke (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
The recent extensive package introduced by the Commission is the most comprehensive reinforcement of economic governance in the EU and the euro area since the launch of the Economic and Monetary Union. Broader and enhanced surveillance of fiscal policies, but also macroeconomic policies and structural reforms are sought in the light of the shortcomings of the existing legislation. New enforcement mechanisms are foreseen for non-compliant Member States. In this very crucial and important package of 6 legislative dossiers this paper tries to identify critical missing or redundant and/or unworkable elements within the Commission package. Moreover, it checks what (if anything) is missing outside and beyond the proposals in order to make the whole package of governance reform complete and workable as, for instance, crisis resolution mechanisms and debt restructuring, EMF, project bonds and Eurobonds. – – Das am 29. September 2010 von der europäischen Kommission vorgestellte und dem Europäischen Parlament vorgelegte ausführliche Maßnahmenpaket stellt die umfassendste Verstärkung einer europäischen 'Economic Governance' seit Einführung der Wirtschafts- und Währungsunion dar. Angesichts der Mängel in der existierenden Gesetzgebung werden dabei eine weiter reichende und verbesserte Überwachung der Fiskalpolitiken, aber auch makroökonomischer Politiken sowie Strukturreformen angestrebt. Neue Durchsetzungsmechanismen für Mitgliedsstaaten, die gegen die Regeln handeln, sind geplant. Im Hinblick auf das sehr wichtige und entscheidende Paket der Kommission, das 6 Gesetzes-Dossiers umfasst, wird in diesem Beitrag versucht, fehlende oder überflüssige und/oder gar nicht verwendbare Elemente zu identifizieren. Weiterhin wird überprüft, was (wenn überhaupt) außerhalb und über diese Vorschläge hinaus noch fehlt, um das gesamte Paket der Governance-Reformen vollständig und durchführbar zu machen. Dies können potenziell Mechanismen zur Krisenlösung und Umschuldung, ein Europäischer Währungsfond, Projekt-Bonds und/oder Euro-Bonds sein.
Keywords: E61; E62; F55; P48; 330; EU governance; European Council; European Financial Stability Facility; European Monetary Fund; policy coordination; scoreboard; Stability and Growth Pact